Protective Role of MerTK in Diabetic Peripheral Neuropathy via Inhibition of the NF-κB Signaling Pathway - Su, Xiaoyang; Chen, Wenting; Fu, Yidan; Wu, Bian; Mao, Fugang; Zhao, Yan; Yang, Qiuping; Lan, Danfeng (Experimental and Clinical Endocrinology & Diabetes, 2024)
Introduction Diabetic peripheral neuropathy (DPN) impacts patient quality of life. In such patients, increased expression of mer tyrosine kinase (MerTK) has been demonstrated; however, its mechanism of action remains unclear. In this study, type 2 diabetes mellitus (T2DM) and DPN models were established in Sprague Dawley rats via low-dose streptozotocin and a high-fat diet and the mode of action of MerTK was examined.Methods MerTK-specific inhibitors were administered by gavage once daily for 2 weeks. Sciatic nerve conduction velocity and nerve structure were measured. The levels of MerTK, nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and relevant biochemical indexes were detected.Results The study revealed upregulation of MerTK expression in T2DM and more so in DPN groups. Inhibiting MerTK led to reduced nerve conduction velocity and further deterioration of sciatic nerve structure, as evidenced by structural morphology. Concurrently, serum levels of total cholesterol, glycated hemoglobin, and triglyceride significantly increased. Moreover, levels of NF-κB increased in both serum and nerve tissue, alongside a significant rise in TNF-α and IL-1β expressions. MerTK could bind to the inhibitor of kappa B kinase beta (Ikbkb) in Schwann cells, establishing Ikbkb as a precursor to NF-κB activation.Discussion Inhibition of MerTK exacerbates neuropathy, indicating its protective role in DPN by suppressing the NF-κB pathway, highlighting a potential new target for its diagnosis and treatment.
Keywords: diabetic peripheral neuropathy; MerTK; NF-κB signaling pathway; inflammatory factors; protective effect